(‐)‐Epicatechin gallate, a metabolite of (‐)‐epigallocatechin gallate in grass carp, exhibits antiviral activity in vitro against grass carp reovirus. (16th January 2020) - Zhang, Yitong; Wang, Hao; Su, Meizhen; Lu, Liqun
Abstract: (‐)‐Epigallocatechin gallate (EGCG), a catechin found in green tea, has been demonstrated to exhibit activity against grass carp reovirus (GCRV). In the current study, we found that EGCG is partially transformed in vivo into (‐)‐epicatechin gallate (ECG), which differs from EGCG only by the absence of a hydroxyl group, and exhibits similar pharmacokinetic behaviour to that of EGCG. ECG is also a major catechin in green tea, but little information on its antiviral activity is available. Therefore, we assessed whether ECG affects GCRV in vitro. We incubated grass carp ( Ctenopharyngodon idellus ) kidney (CIK) cells with ECG and GCRV‐JX01 at different concentrations, and typical cytopathogenic effect (CPE) values were observed for 5 and 10 µg/ml ECG. However, the CPE in 20 µg/ml ECG treatment group was low; no significant CPE was observed for 40 µg/ml ECG treatment; and a high ECG concentration (80 µg/ml) led to stress response in the CIK cells. Western blot results also revealed that ECG suppresses GCRV replication in CIK cells. Thus, the data indicate that ECG, as well as EGCG, exhibits potential as an antiviral agent for aquaculture.